Association of different fractionation schedules for prophylactic cranial irradiation with toxicity and brain metastases-free survival in stage III non-small cell lung cancer: A pooled analysis of individual patient data from three randomized trials. (November 2021) - Witlox, Willem J.A.; Ramaekers, Bram L.T.; Lacas, Benjamin; Pechoux, Cecile Le; Sun, Alexander; Wang, Si-Yu; Hu, Chen; Redman, Mary; van der Noort, Vincent; Li, Ning; Guckenberger, Matthias; van Tinteren, Harm; et al.
Highlights: The risk of toxicity was lower for PCI given in 15 compared to 10 fractions. Both PCI fractionation schedules showed a lower BM incidence compared to observation. Likely, PCI given in 10 or in 15 fractions has similar efficacy. Abstract: We assessed the impact of different PCI fractionation schedules (30 Gy in 10 versus 15 fractions) on brain metastases-free survival (BMFS) and toxicity in stage III NSCLC. Our results suggest that 30 Gy in 10 fractions is associated with increased toxicity, while no conclusive evidence of improving BMFS was seen with this schedule.